Density Functional Theory (DFT) and Natural Bond Orbital (NBO) Analysis of Intermolecular Hydrogen Bond Interaction in "Phosphorylated Nata De Coco - Water" - Sitti Rahmawati; Cynthia Linaya Radiman; Muhamad Abdulkadir Martoprawiro (Indonesian Journal of Chemistry, 2018)
This study aims to study the conformation, the hydrogen bond network, and the stabilities of all the possible intermolecular interactions in phosphorylated nata de coco membrane with water (NDCF-(H2O)n, n = 1-5). Analysis of natural bond orbital (NBO) was performed to measure the relative strength of the hydrogen bonding interactions, charge transfer, particularly the interactions of n-σ * O-H and to take into account the effect on the stabilities of the molecular structure. All calculation were performed using density functional theory (DFT) method, at B3LYP functional level of theory and 6-311 G** basis set. The charge transfer between the lone pair of a proton acceptor to the anti-bonding orbital of the proton donor provides the substantial to the stabilization of the hydrogen bonds. Interaction between NDCF and (H2O)5 was strongest with the stabilization energy of 37.73 kcal/mol, that indicate the ease of donating lone pair electrons. The contributions of each hydrogen bond to the stability of the complex have been analyzed.